1997
DOI: 10.1002/marc.1997.030180410
|View full text |Cite
|
Sign up to set email alerts
|

Alternating terpolymerization of three non‐homopolymerizable monomers

Abstract: The free-radical terpolymerization of maleic anhydride (MSA), isobutyl vinyl ether (VIBE) and anethol (ANE) at 60°C is described. These three monomers do not homopolymerize under the conditions used. Binary copolymers are only obtained from MSA and one of the two investigated donor monomers, whereas the binary copolymerization of VIBE with ANE is not possible. In all terpolymers from these three non-homopolymerizable monomers the MSA content amounts to about 50 mol-%; VIBE is about twice as reactive as ANE. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…28 It is well known that alternating copolymers of vinyl ether and MA can be formed in free-radical polymerization. [29][30][31][32] Our previous report 21 used 1 H nuclear magnetic resonance to show that the molar composition of MA and CVE of the formed copolymer was 1:1, and the 13 C nuclear magnetic resonance spectrum suggested that these monomers were alternately polymerized.…”
Section: Resultsmentioning
confidence: 99%
“…28 It is well known that alternating copolymers of vinyl ether and MA can be formed in free-radical polymerization. [29][30][31][32] Our previous report 21 used 1 H nuclear magnetic resonance to show that the molar composition of MA and CVE of the formed copolymer was 1:1, and the 13 C nuclear magnetic resonance spectrum suggested that these monomers were alternately polymerized.…”
Section: Resultsmentioning
confidence: 99%
“…The actual composition of the copolymers MAn/BuVE was confirmed as 1/1 molar ratio by integrating the peaks corresponding to CH 2 protons of the BuVE lateral chain and the CH protons of MAn at 3.9-3.0 ppm and the peaks of CH of the main ether chain at 4.8-3.9 ppm in 1 H NMR spectra [13][14][15] (Figure 1).…”
Section: Polymer Synthesis and Modificationmentioning
confidence: 99%
“…In the present paper this treatment is applied to the more complex case of three non-homopolymerizable donorand acceptor monomers. Terpolymerizations of these monomers result in terpolymers with alternating sequences of donor-and acceptor monomers, and therefore sometimes are called "alternating terpolymerization" 4) . Because of this strong alternating character there are two types of ternary systems containing acceptor-and donor monomers.…”
Section: Introductionmentioning
confidence: 99%